Prenatal exposure to Bisphenol-A as a risk factor for infant neurodevelopment - Bello-Cortes, Ivan Hazel; García-García, Jose Antonio; Gutiérrez-Aguilar, Manuel; Araiza-Olivera, Daniela; Sánchez-Pérez, Celia; García-Cerón, Gabriela; Morán-Ramos, Sofia; Tovar, Hugo; Bonilla-Brunner, Andrea; García-Arrazola, Roeb (Frontiers in Endocrinology, 2025)
It has been established a chronic human exposure to a particular class of chemicals known as endocrine-disrupting compounds (EDCs). Studies conducted in vitro, in vivo, and in silico have demonstrated that EDCs can disrupt the endocrine system through epigenetic mechanisms. These changes can be heritable and are associated with a wide range of diseases. Since exposure concentrations of these compounds are measured in parts per million (ppm) or even parts per billion (ppb), a critical question arises: does this pose a significant risk to humankind and future generations? We conducted a comprehensive review of human epidemiological data to provide an assessment of the risk of neurodevelopmental disorders in children associated with maternal exposure to Bisphenol A (BPA). BPA is one of the most studied and relevant EDC’s related to food exposure. Our analysis reveals a correlation between BPA exposure during pregnancy and behavioral issues in offspring on 80% of the reviewed articles. Notably, male infants exposed to BPA during the third trimester exhibited a heightened risk. Our findings highlight the importance of considering potential new health regulations aimed at safeguarding the fetal environment and reducing the risk of neurodevelopmental disorders in children.